Approaches of Finite Element Analysis to Study Fatigue Analysis of Rail-Wheel Contact for Light Rail Transit - Tawfik, MN; Padzi, M.M; Shahrum; Hapaz, H.; Zahar, Mazli; Firdaws, M. Nur (International Journal of Integrated Engineering, 2022)
Rolling contact fatigue (RCF) is one of the main rail failure due of repeated stresses at rail-wheel contact. The types of defects of RCF such as spalling, squat and head checking occur at surface of rail as possible lead to catastrophic for train derailment. As to reduce the cost of maintenance in using preventative maintenance than corrective maintenance where it crucial to predict the rail fatigue failure through simulation. The objective of this research paper was to predict the cracks at rail surface in 3-dimensional through finite element analysis and in compared results with Hertz theory, also to count circles of fatigue failure with 80000 N against rail. The rail profile selection was R260 as standard rail for light rapid transit. Results demonstrated that the highest von mises stress located at contact patch of rail-wheel, different percent of von mises stress & contact pressure and predicted the rail fatigue regards 339300 circles. Furthermore, this research study has not yet reported and discussed in previous studies for light rapid transit.